Sociologies of Formality and Informality - Mica, Adriana (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2015)
The way sociology frames the relation between formality and informality is not only complex and multifaceted, but has also evolved over time. This volume offers contributions by international authors that illustrate distinct types of theoretical framings and present various sites of inquiry. It proposes a typology comprising: the sociology of informally embedded formality, the sociology of formally embedded informality, the sociology of the interaction between formality and informality and the sociology of the emergence and transformation of formality and informality
Description based on publisher supplied metadata and other sources
Keywords: Philosophie; Organizational sociology; Social institutions; Social systems; Sociology -- Philosophy; Organisationssoziologie; Informelle Beziehung; Soziologie; Institution -- Soziologie; Konferenzschrift